Нові асоціації лучної рослинності з рівнинної частини України - Куземко, А.А. (Український ботанічний журнал, 2012)
Описаны две новые для науки ассоциации класса Molinio-Arrhenatheretea — Festucetum praten sis-regelianae (союз Festucion pratensis) и Agrostio caninae-Alopecuretum pratensis (союз Alo pecurion pratensis). Приводятся диагностические, константные и доминантные виды ассоциаций, характеристика их местообитаний, особенности географического распроcтранения. Представлены также фитоценотические таблицы обеих ассоциаций. Two new for science associations of Molinio-Arrhenatheretea class are described, Festucetum pratensis-regelianae (Festucion pratensis alliance) and Agrostio caninae-Alopecuretum pratensis (Alo pe cu ri on pratensis alliance). The diagnostic, constant and dominant species of the associations, characteristics of their habitats and peculiarities of the geographic distribution are considered. The phytocoenotic tables of both associations are presented.